Antibiotic Sensitivity Pattern of Bacterial Isolates from Clinical Specimens of Patients Admitted in Intensive Care Unit - Pokharel, Khilasa; Dawadi, Bishwa Raj (Birat Journal of Health Sciences, 2021)
Introduction: Antibiotics resistance is increasing nowadays. Factor to antibiotic resistance is its misuse. There is no national guideline for use of antibiotics. Objective: Study was conducted to determine bacteriological profile, and the bacterial antibiotic sensitivity pattern of the pathogens isolated from patients in intensive care unit. Methodology: Study was conducted between 1st October 2020 and 30th March 2021. The samples collected from Intensive care units patients were processed in Microbiology Laboratory following Clinical and Laboratory Standard Institute guideline. Organisms were identified morphologically and biochemically and antibiotic sensitivity pattern was determined by disc diffusion methods. Result: Out of total 397 samples, only 46 were found to be culture positive, of which 32 (69.56%) were gram negative organisms and 14 (30.43%) were gram positive organisms. Out of gram negative organisms Klebsiella pecies 10 (21.73%) were predominant which is more sensitive to colistin, polymyxin B and tigecycline. Among gram positive organisms Staphycoccus aureus 12 (85.71%) was found more sensitive to Vancomycin than others. Conclusion: It is concluded that Klebsiella species and Staphylococcus aureus were predominant pathogens isolated from the patients. Regular surveillance of antibiotic sensitivity pattern and stewardship program will be useful in treating patients in Intensive care unit.